Flexible Working Arrangement (FWA) Model: Reducing Congestion Levels and Work Stress and Increasing Work Productivity - Sultan, Zulkifli
Rozbor vplyvu flexibilnej práce systému usporiadania (FWA) pri znižovaní dopravných zápch, znižovaní pracovného stresu a zvýšení produktivity práce.